Pengaruh Penambahan Pati Kacang Hijau pada Pembuatan Processed Cheese dengan Koagulan Ekstrak Buah Mengkudu Terhadap Rendemen, Intensitas Warna, dan Firmness - Yuliastri, Desi; Putranto, Wendry Setiyadi; Utama, Dicky Tri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Cheese is a food produced through the process of coagulation and separation of curd and whey. Processed cheese has become a favorite of many people due to its unique and practical characteristics. The complex process of cheese making involves the use of rennet enzyme as one of the key components. Noni contains a significant amount of protease enzyme that can be used as a substitute for rennet. This study aimed to determine the effect of mung bean starch addition on yield, color, and firmness of processed cheese coagulated with noni fruit juice. This study used a Completely Randomized Design with four treatments of mung bean starch concentration (P0=0%, P1=2,5%, P2=5%, P3=7,5%) and five replication. Analysis of variance was carried out after the data was obtained and continued with Duncan's Multiple Range test. The results showed that the addition of mung bean starch did not give a significant effect on color, but gave a significant effect on yield and firmness. The use of 7,5% mung bean starch concentration produced the best processed cheese with a yield of 70,16%, color including L* of 58,03, a* of -0,22, b* of 18,48, and firmness of 67,73N.